Principles of Security and Trust Third International Conference, POST 2014, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2014, Grenoble, France, April 5-13, 2014, Proceedings - Abadi, Martín; Kremer, Steve (Security and Cryptology, 2014)
This book constitutes the refereed proceedings of the Third International Conference on Principles of Security and Trust, POST 2014, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2014, Grenoble, France, in April 2014. The 15 papers presented in this volume were carefully reviewed and selected from 55 submissions. They are organized in topical sections named: analysis of cryptographic protocols; quantitative aspects of information flow; information flow control in programming languages; cryptography in implementations and policies and attacks.